1993
DOI: 10.1159/000107291
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Patterns of Plaques and Tangles in Alzheimer's Disease Do Not Support the 'Cascade Hypothesis'

Abstract: In Alzheimer''s disease (AD), the ''Cascade hypothesis'' proposes that the formation of paired helical filaments (PHF) may be causally linked to the deposition of β/A4 protein. Hence, there should be a close spatial relationship between senile plaques and cellular neurofibrillary tangles in a local region of the brain. In tissue from 6 AD patients, plaques and tangles occurred in clusters and individual clusters were often regularly spaced along the cortical strip. However, the clusters of plaques and tangles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…The best evidence for a central role of tau in AD pathogenesis was the result of a series of studies by Heiko and Eva Braak and colleagues that demonstrated a progressive sequence of neurofibrillary pathology illustrating the spread of NFT in the CNS [18]. This work established a timeline for NFT lesion progression through the CNS in AD that was tightly correlated to the initial presentation and progression of clinical symptoms [46,47]. This "Braak pattern" of NFT development begins in the limbic cortex of the temporal lobe and progresses to association (polymodal) areas of the neocortex, leaving primary sensory and motor areas unaffected until end stage disease has set in.…”
Section: Tau -The Amyloid Cascade Hypothesis Is Incompletementioning
confidence: 99%
“…The best evidence for a central role of tau in AD pathogenesis was the result of a series of studies by Heiko and Eva Braak and colleagues that demonstrated a progressive sequence of neurofibrillary pathology illustrating the spread of NFT in the CNS [18]. This work established a timeline for NFT lesion progression through the CNS in AD that was tightly correlated to the initial presentation and progression of clinical symptoms [46,47]. This "Braak pattern" of NFT development begins in the limbic cortex of the temporal lobe and progresses to association (polymodal) areas of the neocortex, leaving primary sensory and motor areas unaffected until end stage disease has set in.…”
Section: Tau -The Amyloid Cascade Hypothesis Is Incompletementioning
confidence: 99%
“…The ACH is often regarded as the 'conclusive model' of the aetiology of early-onset FAD, and sporadic AD (SAD), a more complex disorder caused by a variety of factors, but resulting from essentially the same pathological cascade [42,127]. Since its publication there have been observations difficult to reconcile with the ACH and concerns whether it completely describes AD pathogenesis [11,90]. First, transgenic mice, in which genes overexpress amyloid precursor protein (APP), do not reproduce the predicted cascade [39,90].…”
Section: Introductionmentioning
confidence: 99%
“…First, transgenic mice, in which genes overexpress amyloid precursor protein (APP), do not reproduce the predicted cascade [39,90]. Second, SP and NFT are separated in brain both spatially [11] and temporally [39,82] questioning the pathogenic link between them. Third, Aβ and tau could be the reactive products of neurodegeneration rather than their cause, arising as a consequence of oxidative stress [126].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also suggested that SP and NFT occur in distinct but independently distributed patterns in AD [19,93]. Studies of the spatial patterns of SP and NFT show them to be clustered, the clusters often being regularly distributed parallel to the pia mater [8].…”
Section: Appmentioning
confidence: 99%